2016
DOI: 10.1136/jmedgenet-2016-104259
|View full text |Cite
|
Sign up to set email alerts
|

Congenital valvular defects associated with deleterious mutations in thePLD1gene

Abstract: The findings support a role for PLD1 in normal heart valvulogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…Sequences were determined by HiSeq2000 (Illumina, San Diego, CA, USA). The full sequencing methodology and variant interpretation protocol were previously described (Ta-Shma et al 2017). Following reads alignment to human genome (hg19), variant calling and filtration, all remaining variants were heterozygous, and there were no variants in any of the genes of the Clinical Genomic Database (CGD) that could fit an Xlinked or autosomal recessive or dominant mode of inheritance (Solomon et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Sequences were determined by HiSeq2000 (Illumina, San Diego, CA, USA). The full sequencing methodology and variant interpretation protocol were previously described (Ta-Shma et al 2017). Following reads alignment to human genome (hg19), variant calling and filtration, all remaining variants were heterozygous, and there were no variants in any of the genes of the Clinical Genomic Database (CGD) that could fit an Xlinked or autosomal recessive or dominant mode of inheritance (Solomon et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Variant interpretation protocol has been previously described. 5 WES of affected individual 5 and her parents and affected individual 6 was performed on exon targets captured using SureSelect Human All Exon 50 Mb Kit V.4 (Agilent Technologies, Santa Clara, CA, USA). Sequences were determined by HiSeq2000 (Illumina, San Diego, CA, USA).…”
mentioning
confidence: 99%
“…The full sequencing methodology and variant interpretation protocol were previously described. 5 Clinical exome sequencing of affected individual 7 and her parents was performed at Ambry Genetics as previously described. 6 All the procedures were in accordance with the ethical standards of the responsible committee on human experimentation (institutional and national); proper informed consent was obtained from all guardians.…”
mentioning
confidence: 99%
“…In the past years, several genetic studies were also performed in patients with familial MR due to MVP and identified three possible loci for autosomal-dominant MVP on chromosomes 16 (MMVP1), 11 (MMVP2) and 13 (MMVP3). [13][14][15] Furthermore, DCHS1 and PLD1 have been linked to autosomal MVP 16,17 and mutations in the filamin A (FLNA) gene have been identified to cause a X-linked form of MVP. 18 In line with these findings, the present study observed different distributions of affected family members between families (Figure 3).…”
Section: Heritability Of Mvp and Mrmentioning
confidence: 99%